Energy-Aware Frameworks in Cloud Data Centers to Manage Workload and Diminish Power Consumption: A Survey - Patel, Rajesh P; Makawana, Ramji (International Journal of Computer Sciences and Engineering, 2018)
Cloud Computing is a service model for enabling convenient, on-demand network access to a shared pool of configurable computing resources which can be rapidly provisioned and released. In cloud data centers various computing resources like servers, network devices and cooling systems which constantly evolve in size and in complexity so it consumes large amount of energy which increase extensive power consumption in data centers. As cloud data center resources are not optimized for their maximum utilization, they consume more power so it needs to consolidate virtual machines (VMs) of servers of data center which helps to optimize the usage of cloud resources hence reduce the energy consumption. By considering the optimized power consumption of various data center resources, the researchers have proposed various methodologies and algorithms to reduce power consumption in servers and network devices. In this paper, we have done insightful study of the modern techniques on data center’s power model of servers, network components also on VM overload/under-load detection, VM selection and VM placement or consolidation of VMs which optimize the utilization of data center’s servers for power model which and reduce energy consumption in data center.